The people's voice: celebrating the Janey Buchan political song collection (Glasgow Left in the Dark Records, 2013)
Compilation CD - The People's Voice: Celebrating the Janey Buchan Political Song Collection. Features Alasdair Roberts, the McCluskey Brothers, Jo Mango, Amanda Lucas, The Hellfire Club, Dave Feathertsone, Kim Moore and the Glasgow Madrigirls. The featured artists have joined a range of others in compiling an album of songs from the Collection which is housed at the University of Glasgow.